A cytogenetic study of R. constantinopolitanus and R. sericeus (Ranunculaceae) in Iran. Issue 1 (21st April 2016) - Rastipisheh, Sareh; Nemati, Somayeh; Pakravan, Maneezheh; Tavassoli, Akhtar; Bolourian, Saman
Abstract : With 600 species Ranunculus is the largest genus in Ranunculaceae, and has a broad global distribution. We studied the karyotypes of R. constantinopolitanus and R. sericeus species of Ranunculaceae and identified their symmetry level. New chromosome numbers of 2 n = 21 (Nodeh woods population) and 2 n ca . 63 (Javaherdeh population) are reported for R. constantinopolitanus . Two different populations of R. sericeus had two different chromosome results. We investigated morphological and karyological studies along with pollens micromorphology. Different populations of R. constantinopolitanus and R. sericeus, with different chromosome numbers showed morphological and micromorphological differences. Therefore, we considered the two populations of R. sericeus as cytotypes. There was a correlation between the studied morphological characters and pollen size with ploidy levels in the two R. constantinopolitanus populations.